Almost periodic solutions of fuzzy shunting inhibitory CNNs with delays - Kashkynbayev, Ardak; Koptileuova, Moldir; Issakhanov, Alfarabi; Cao, Jinde (AIMS mathematics, 2022)
In the present paper, we prove the existence of unique almost periodic solutions to fuzzy shunting inhibitory cellular neural networks (FSICNN) with several delays. Further, by means of Halanay inequality we analyze the global exponential stability of these solutions and obtain corresponding convergence rate. The results of this paper are new, and they are concluded with numerical simulations confirming them.